2020
DOI: 10.3389/fimmu.2020.00010
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Extracellular Vesicles to the Arthritic Joint Using a Damaged Cartilage-Specific Antibody

Abstract: The targeted delivery of therapies to diseased tissues offers a safe opportunity to achieve optimal efficacy while limiting systemic exposure. These considerations apply to many disease indications but are especially relevant for rheumatoid arthritis (RA), as RA is a systemic autoimmune disease which affects multiple joints. We have identified an antibody that is specific to damaged arthritic cartilage (anti-ROS-CII) that can be used to deliver treatments specifically to arthritic joints, yielding augmented ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 34 publications
(48 reference statements)
0
28
0
Order By: Relevance
“…Thereby, they may be considered as physiological targeting mediators ( Figure 1 ). Furthermore, the use of antigen-specific antibodies or LCs greatly increases the specificity of tissue targeting by EVs [ 117 ].…”
Section: Perspectives In Manipulating Evs For Therapeutic Applicatmentioning
confidence: 99%
“…Thereby, they may be considered as physiological targeting mediators ( Figure 1 ). Furthermore, the use of antigen-specific antibodies or LCs greatly increases the specificity of tissue targeting by EVs [ 117 ].…”
Section: Perspectives In Manipulating Evs For Therapeutic Applicatmentioning
confidence: 99%
“…With the addition of a range of EV surface receptors, such as immunoglobulins, lectins, MHC receptors, and viral proteins, it is possible to promote the selective recruitment of EVs to a specific tissue, site of injury, or cell population [ 125 ]. In fact, work from our group has demonstrated that neutrophil-derived EVs, which display anti-inflammatory activity, can be loaded with therapeutic cargo including anti-TNF-α as well as IL-10 and targeted to arthritic joints using cartilage specific antibodies to improve experimental arthritis ( Figure 2 ) [ 151 , 152 , 153 ].…”
Section: Therapeutic Potential Of Manipulating Evsmentioning
confidence: 99%
“…Using a variant of anti-ROS-CII, bound to viral IL-10 via a matrix metalloproteinase cleavable linker region (anti-ROS-CII-vIL-10), EVs were able to release an anti-inflammatory payload upon arrival to the injured joint. PMN-EVs co-engineered to express both anti-ROS-CII-vIL-10 and anti-TNF antibodies were shown to greatly reduce pro-inflammatory cytokine gene expression and enhance cartilage anabolism; to the extent whereby CIA joints treated with modified PMN-EVs were similar to healthy joints based on gross architectural appearance [ 151 , 154 ].…”
Section: Figurementioning
confidence: 99%
“…We previously developed a panel of human single chain fragment variable (scFv) that bind speci cally to oxidative post-translationally modi ed collagen type II (oxPTM-CII) (12). We showed that anti-oxPTM-CII: i) binds speci cally to arthritic cartilage from patients with RA and OA; ii) stains cartilage in murine models of in ammatory arthritis (antigen induced arthritis (AIA) and OA, namely DMM; iii) localizes in the arthritic joint in vivo in a mouse model of AIA and DMM following systemic administration of labelled anti-oxPTM-CII with Alexa Fluor 680 or Cy5.5 (12,13); and iv) was able to target therapeutic scaffold speci cally to arthritic joint (14).…”
Section: Introductionmentioning
confidence: 99%